The importance of postgraduate training for the pharmaceutical sector, in times of great challenges - Porras Navarro, Marta Eugenia (2021)
In this article, the authors offer a synthesis and reflection of scientific disclosures about the importance of postgraduate training, the current challenges of the pharmaceutical sector and the relevant training options for pharmacists, which reflects the learning needs perceived by the pharmacy guild and its employers, along with the benefits and motivations of continuous training, according to international investigations. This research provides scientific information for the development of current training proposals based on the pharmacist’s postgraduate education needs, according to professionals and employers. In conclusion, the higher education system, universities, and employers are Essential to obtain a training project according to the needs of each country. Likewise, it is important to mention that postgraduate training is a pillar for achieving more equitable health policies at a times of great challenge in the pharmaceutical sector, where the most significant contribution of the pharmacist is being part of drugs and vaccines development that allow governments and international organizations to fairly distribute these to the entire population.